FGFR3-TACC3 is an oncogenic fusion protein in respiratory epithelium. Issue 46 (15th November 2018) - Best, Sarah; Harapas, Cassandra; Kersbergen, Ariena; Rathi, Vivek; Asselin-Labat, Marie-Liesse; Sutherland, Kate
Abstract Structural rearrangements of the genome can drive lung tumorigenesis through the generation of fusion genes with oncogenic properties. Advanced genomic approaches have identified the presence of a genetic fusion between fibroblast growth factor receptor 3 (FGFR3 ) and transforming acidic coiled-coil 3 (TACC3 ) in non-small cell lung cancer (NSCLC), providing a novel target for FGFR inhibition. To interrogate the functional consequences of the FGFR3–TACC3 fusion in the transformation of lung epithelial cells, we generated a novel transgenic mouse model that expresses FGFR3–TACC3 concomitant with loss of thep53 tumor suppressor gene. Intranasal delivery of an Ad5-CMV-Cre virus promoted seromucinous glandular transformation of olfactory cells lining the nasal cavities of FGFR3–TACC3 (LSL –F3T3 ) mice, which was further accelerated upon loss ofp53 (LSL –F3T3 /p53 ). Surprisingly, lung tumors failed to develop in intranasally infectedLSL –F3T3 andLSL –F3T3 /p53 mice. In line with these observations, we demonstrated that intranasal delivery of Ad5-CMV-Cre induces widespread Cre-mediated recombination in the olfactory epithelium. Intra-tracheal delivery of Ad5-CMV-Cre into the lungs ofLSL –F3T3 andLSL –F3T3 /p53 mice, however, resulted in the development of lung adenocarcinomas. Taken together, these findings provide in vivo evidence for an oncogenic function of FGFR3–TACC3 in respiratory epithelium.